Continuous Glucose Monitoring in Diabetic Women Following Antenatal Corticosteroid Therapy: A Pilot Study - Refuerzo, Jerrie S.; Garg, Ambica; Rech, Barbara; Ramin, Susan M.; Vidaeff, Alex; Blackwell, Sean C. (American Journal of Perinatology, 2012)
To compare the timing, duration, and severity of corticosteroid-associated hyperglycemia in pregnant women with and without diabetes mellitus (DM). An observational study was conducted of pregnant women with DM and controls who received corticosteroids. Median glucose levels were calculated over 4-hour intervals after the first dose of corticosteroid with a continuous glucose monitor. A glucose level increase of at least 15% above baseline was considered significant. Nine pregnant women participated in this study (six with DM and three without DM). Elevations of glucose levels occurred at hour 20, 44, and 68 in both groups and lasted for up to 4 hours. In those with DM, glucose levels increased 33 to 48%, whereas in those without DM, glucose levels rose 16 to 33%. Several, relatively short episodes of glucose elevation occur in response to corticosteroids, and are more pronounced in diabetic women.
Keywords: continuous glucose monitoring; corticosteroids; diabetes